Forecasting contrasting coastal and estuarine hydrodynamics with OPENCoastS. (September 2021) - Oliveira, Anabela; Fortunato, André B.; Rodrigues, Marta; Azevedo, Alberto; Rogeiro, João; Bernardo, Samuel; Lavaud, Laura; Bertin, Xavier; Nahon, Alphonse; de Jesus, Gonçalo; Rocha, Miguel; Lopes, Pedro
Abstract: Robust and accurate coastal forecasts require models to represent the relevant processes, prediction computational tools and reliable computational resources. OPENCoastS is a free, open-source WebGIS platform to develop on-demand hydrodynamic forecast systems that started as a simple 2D engine. OPENCoastS provides a visualization and download interface with in-situ and Sentinel satellite data comparison. 2D tidal, 2D wave & current interaction and 3D baroclinic flows are now included, forced by several atmospheric, oceanic and riverine forcings. Four applications demonstrate OPENCoastS' capacity. The prediction of the 2020 typhoon season in Taiwan illustrates the use of the service using only large-scale public data. An application to the Bay of Biscay shows the importance of waves on extreme water levels during storms. A nearshore deployment in Figueira da Foz harbor assesses the impact of bathymetry on coupled wave and current circulation. 3D baroclinic circulation forecasts in Tagus estuary are validated by independent data. Graphical abstract: Image 1 Highlights: Web platform to generate on-demand forecast systems for multiple circulation options. Open source software at https://opencoasts.ncg.ingrid.pt/, using EOSC resources. Forced by GFS, WRF or ARPEGE (atmosphere), CMEMS or FES2014 (ocean) and WW3 (waves). Data/model comparison with Copernicus Sentinel data and in-situ EMODnet field data.